Effect of Oak Chips Application on Phenolic Compounds of Wine Vinegars at Different Maturation Times - Mustafa Bayram; Semra Topuz; Cemal Kaya; Rahmi Ertan Anlı (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to investigate the effects of oak chips-supplementations on phenolic compound profiles of grape vinegar samples. Total acidity, volatile acids, non-volatile acids, pH, dry extract, ash, color, alcohol, total phenolic compound, individual phenolic compounds and aroma compounds of un supplemented control (UC) samples and oak chips-supplemented (OCS) samples were analyzed at the 0th, 1st and 3rd months of ageing. Total phenolic compound of UC vinegar samples was measured as 1256.50 mg GAE/L at the end of the 3rd month. Total phenolic compound of OCS vinegar samples was measured as 1521.03 mg GAE/L at the end of the 1st month and as 1470.67 mg GAE/L at the end of the 3rd month. Gallic acid, catechin and vanillic acid contents of UC vinegar samples were respectively measured as 8.43 mg/L, 22.26 mg/L and 1.78 mg/L at the end of the 3rd month. Gallic acid, catechin and vanillic acid contents of OCS vinegar samples were respectively measured as 19.12 mg/L, 17.98 mg/L and 2.58 mg/L at the end of the 3rd month. The 3-hydroxy-2-butanone, hexadecanoic acid methyl ester, 9,12-octadecadienoic acid methyl ester and 9-octadecanoic acid methyl ester quantities increased at the end of the 3rd month with oak chips-supplementation to ageing process. It was observed that oak chips-supplementation increased total phenolic compound and some individual phenolics of grape vinegar samples.